2020
DOI: 10.3390/ijerph17103747
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of COVID-19 on Tourist Satisfaction with B&B in Zhejiang, China: An Importance–Performance Analysis

Abstract: After the outbreak of COVID-19 (especially in the stage of tourism recovery), the bed and breakfast (B&B) tourism industry faced big challenges in improving its health strategies. B&Bs are very important for the tourism industry in China and many other countries. However, few studies have studied the impact of B&Bs, under COVID-19, on tourism in China. Our paper is among one of the first studies to investigate the impact of COVID-19 on tourist satisfaction with B&Bs in China. The work/travel re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
63
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(88 citation statements)
references
References 105 publications
(135 reference statements)
0
63
0
7
Order By: Relevance
“…COVID-19) as well as extreme weather conditions. Travellers are expressing a preference for non-communal spaces like private bathrooms and natural, outdoor space (CCG, 2020;Hong et al, 2020). Emerging trends in camping (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…COVID-19) as well as extreme weather conditions. Travellers are expressing a preference for non-communal spaces like private bathrooms and natural, outdoor space (CCG, 2020;Hong et al, 2020). Emerging trends in camping (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Airbnb), and traditional (e.g. hotel) accommodations is the novel coronavirus 2019 where travellers prefer locations without communal spaces that facilitate social distancing (Craig, 2020;CCG, 2020;Dolnicar & Zare, 2020;Hong et al, 2020). Many campsites were able to remain open due to outdoor, natural settings that provide ample distance from others (Centers for Disease Control [CDC], 2020; Gossling et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Prior to the novel coronavirus 2019 (COVID-19), interest in camping—an outdoor accommodation and form of recreation ( Craig, 2019 )—among experienced and new campers was evident ( CCG, 2019 ). Present day travelers prefer distance from others, natural space, and outdoor recreation ( Hong et al, 2020 ; Rice et al, 2020 ), three drivers of camping decisions ( CCG, 2020 ). Camping is well-positioned with domestic accommodations showing signs of recovery as travel restrictions loosen ( Gossling et al, 2020 ; Ma et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Studies showed that the economic impact caused by severe acute respiratory syndrome (SARS) will produce psychological morbidities in individuals who are directly or indirectly exposed to life-threatening situations [21]. The occurrence of such psychological morbidities among workers can impact their daily functions and lead to immediate economic and physiological consequences, such as lost job productivity, depression, and anxiety [22,23].…”
Section: Introductionmentioning
confidence: 99%